A comparison of high-performance football coaches experiencing high- versus low-burnout symptoms across a season of play: Quality of motivation and recovery matters - Bentzen, M.; Lemyre, N.; Kenttä, G. (International Sport Coaching Journal, 2017)
The purpose of the current study was to provide insights in how and why four head coaches in elite football experienced being either high or low in burnout symptoms (BS) during a competitive season. A longitudinal sequential quantitative-qualitative mixed method approach was used to enhance the understanding of coaches` experiences. First, data were collected using online questionnaires at the start and at the end of the competitive season with all coaches working at the Norwegian Elite Football League level. Second, in-depth interviews were conducted with four head coaches who were purposefully selected based on having the two highest and the two lowest burnout scores across the season compared with the overall sample. A quantitative approach was used to explore whether these four coaches differed when compared with the overall population on the associated variables: performance, budget, quality of motivation, perceived workload, work-home-interference (WHI), and recovery. A qualitative approach helped gain more insight in the experiences these four coaches had with possible onset variables. Analyses comparing the two sets of coaches, indicated no difference related to performance, budget and workload. However, the motivational profile, WHI, and ability to meet recovery demands were variables that contributed to explain differences in coaches` BS.